Diversidad y abundancia del recurso hidrobiológico en el lago Aripari en épocas de vaciante y creciente, Río Marañon, Loreto Perú - Carranza López, Nidia Violeta (2024)
The present study evaluated fish for human consumption from Lake Aripari, located in the Marañón River basin, in order to analyze the diversity and abundance of species, as well as the physical-chemical characterization of the lake. The captures were carried out in two periods: emptying (September - October) and increasing (November - December) of 2022, in 14 sampling stations. Trawl nets, cast nets and hand nets were used for captures, and 833 fish belonging to 3 orders and 16 families were obtained. In terms of diversity, greater richness was observed during the growing season (503 species), compared to the emptying season (330 species). The order Characiformes and the family Characidae predominated in both seasons. The most abundant species were Prochilodus nigricans (boquichico) and Potamorhina altamazonica (llambina). The abundance of fish was greater during the flood, with 503 specimens, while during the low, 330 specimens were recorded. The smallest fish, less than 10 cm, were the most abundant. In terms of dominance, it was observed that the EM1 of Lake Aripari showed greater richness and abundance in both seasons. During emptying, the concentration of carbon dioxide (CO2) increased, which caused an increase in water hardness, alkalinity and pH, which influenced electrical conductivity.